Mapping of Landslide Hazard Distribution in Alo Watershed Gorontalo Regency - Risman Jaya; Ahmad Syamsu Rijal (Universitas Negeri Gorontalo, 2020)
Landslide occurrence can be influenced by physical factors and human activities. Thus, research related to the provision of information about landslide distribution in Alo watershed is needed as a basis in enhancing community preparedness in dealing with disasters. The method used in this study is the scoring method based on the Minister of Public Works Regulation No.22 / PRT / M / 2017 which is processed through a geographical information system through the overlay of all physical parameters. The result shows that the Alo watershed area is divided into three vulnerability categories.